Variación cualitativa y cuantitativa de fitoplancton en estanques durante la etapa de engorde de cultivo de camarón blanco (litopenaeus vannamei) - Pesantez Enrique, Geovanny; Rodríguez Beltrán, Lisbeth Anahi (Machala : Universidad Técnica de Machala, 2023)
In semi-closed aquaculture systems for the production of L. vannamei, microalgae play a fundamental role in the production of oxygen through the photosynthesis, being at the same time a potential food source, which highlights their presence for the ecological balance of the ponds. Phytoplankton in a pond can be composed of various microalgal groups, and develop in all aquatic ecosystems in response to various physicochemical factors, therefore, the objective of the present study was to evaluate the qualitative and quantitative variation of phytoplankton in aquaculture ponds. In order to fulfill this objective, data were recorded from 3 ponds during a shrimp farming cycle, in the shrimp farm “SATUKIN S.A” located in Yaguachi, province of Guayas. Both microalgae type and concentration were identified and quantified, respectively. The main groups present were chlorophytes, cyanophytes, diatoms, dinoflagellates (and others), which were identified by means of microscopy techniques, which included identification guides for phytoplankton, and a Neubauer chamber. As a counterpart, data on the concentration of both N and P were obtained by means of spectrophotometry, as well as the N:P ratio. Furthermore, the incidence of N and P on the phytoplanktonic composition and concentration was evaluated. The results showed a seasonal variation in the composition of phytoplankton throughout the culture period of L. vannamei, where chlorophytes and cyanophytes where the dominating groups in the ponds, with variations in their abundance related to the N:P ratio. These results highlight the complex interaction between nutrients and microalgae in aquatic systems, and their importance for understanding and managing the water quality in aquatic ecosystems.
En los sistemas semi-cerrados destinados al cultivo de L. vannamei, las microalgas desempeñan un papel fundamental en la producción de oxígeno mediante procesos fotosintéticos, además son una fuente potencial de alimento lo que destaca su presencia para el equilibrio ecológico de los estanques. El fitoplancton se puede componer de diversos grupos microalgales, y desarrollar en todos los ecosistemas acuáticos de acuerdo a varios factores fisicoquímicos, por tal razón, el objetivo del presente estudio fue evaluar la variación cualitativa y cuantitativa del fitoplancton en estanques acuícolas. Para tal efecto se registraron datos de 3 estanques durante el ciclo de cultivo de camarón, en la empresa camaronera “SATUKIN S.A” ubicada en el cantón Yaguachi de la provincia del Guayas. Se identificó la concentración de microalgas y, a su vez se clasificó los principales grupos presentes (clorofitas, cianofitas, diatomeas, dinoflagelados y otros grupos) mediante la aplicación de técnicas de microscopía, que incluían cámara de Neubauer, y guías de identificación para fitoplancton. Como contraparte, se obtuvieron datos de la concentración de nitrógeno y fósforo, mediante la aplicación de espectrofotometría, al igual que la relación N:P, y se evaluó la incidencia de los nutrientes (N y P) en las composición y concentración fitoplantónica. Los resultados revelaron una variación estacional en la composición del fitoplancton en la etapa de engorde de L. vannamei, en donde las clorofitas y las cianofitas dominaron en los estanques, con variaciones en su abundancia relacionadas con la relación N:P. Estos resultados destacan la compleja interacción entre nutrientes y microalgas en sistemas acuáticos y su importancia para comprender y gestionar la calidad del agua en los ecosistemas acuáticos.
Keywords: FITOPLANCTON; NUTRIENTES; DOMINANCIA; OXIGENO DISUELTO